Narrativas de professoras da educação infantil sobre suas práticas docentes em matemática: contribuições de grupos de pesquisa - Duarte, Raissa Alexandra Lopes (Universidade Federal de São Carlos, 2025)
Once upon a time, there were Alice (not the one from Wonderland) and Dorothy (not the one from Oz), but two dedicated teachers from the municipal public school system, passionate about mathematics. Alice spent her childhood on a farm surrounded by nature, amid the affection of her family and playing with her two sisters. Dorothy grew up in a bustling, urbanized capital city, where she shared her daily life with two brothers and the constant presence of her mother. One day, both decided to follow paths far from their origins. They faced challenges, took unexpected routes, but ended up rediscovering the meaning of their trajectories in teaching. Children, education, and research groups welcomed them back, allowing their enchantment with the profession to flourish in a different way. This thesis narrates the formative adventures of these two teachers, guided by the following research question: How do teachers who participate in research groups strengthen their teaching practices in Early Childhood Education when addressing mathematical knowledge? The general objective of the research is to understand the strengthening of teaching practice in relation to the mathematical knowledge of Early Childhood Education teachers, based on narratives about their experiences in research groups. As specific objectives, this research problematizes aspects of the formative processes and knowledge construction revealed by early childhood education teachers in relation to mathematical knowledge in childhood through their oral narratives; and identifies evidence of the strengthening of these teachers' pedagogical practice in the pedagogical work developed with early childhood education children involving mathematical knowledge. To answer this question and meet the research objectives, I mapped the research groups registered in the CNPq Directory that address Mathematics Education in Basic Education, selecting those that specifically address Early Childhood Education. It was during this process that I met Alice and Dorothy, through narrative interviews conducted online. Based on research with narratives and hermeneutics, the analyses were organized into narrative notes, based on the contributions of Jovchelovitch and Bauer (2002) and Clandinin and Connelly (2015), highlighting the intertwining and distancing that emerged from the stories of these teachers. With Alice and Dorothy, I learned about the power of continuous training movements in research groups and how these collaborative spaces impact pedagogical work in early childhood education. Both invite us to (re)think mathematical knowledge in a sensitive and situated way—a mathematics that is possible, lived, and experienced by children in their daily lives. They taught me that, in early childhood education, “there are no students or homework, but experiences; there are no tasks, but experiences.” Thus, mathematics takes shape and meaning in experience—a meaningful mathematics that arises from listening to children and is built on what they live and feel.
Narratives from early childhood education teachers about their teaching practices in mathematics: contributions from research groups
Keywords: Educação infantil; Educação matemática; Narrativas; Grupos de estudos e pesquisa; Child education; Mathematics education; Narratives; Study and research groups; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade